Acute renal failure in children with pre-chemotherapy advanced stage Burkitt's lymphoma - Olowu, W A; Elusiyan, J; Badejo, S A; Adenowo, O A (African Journal of Nephrology, 2023)
Background: Outcome of treatment of Burkitt's lymphoma - associated acute renal failure (BLARF) without dialysis is rather poor. This was a retrospective comparative study aimed at determining the outcome of two different treatment protocols tried on children with BLARF in two separate eras. Methods: One group of patients was assigned to treatment protocol A (TPA) and the other to treatment protocol B (TPB). TPA consisted of oral allopurinol, intravenous (IV) cyclophosphamide, vincristine, methotrexate, frusemide, 8.4% sodium bicarbonate and intrathecal (IT) methotrexate. TPB consisted of oral allopurinol, alternate days IV infusion of low dose cyclosphosphamide (125mg/m2 x4 doses), IT methotrexate, oral calcium lactate, IV calcium gluconate, salbutamol, insulin and IV infusion of frusemide, sodium bicarbonate and glucose. Results: There were 16 BLARF patients (12 boys) aged 6-14 years. Nine of 16 underwent TPA while 7 underwent TPB. Three of 9 TPA patients had stage C Burkitt's lymphoma (BL) while 6 had stage D BL. Five and 2 patients in TPB had stages C and D BL, respectively (P=0.1371). All the 16 patients had postchemotherapy tumour lysis syndrome (TLS). Six of 9 patients in TPA died from TLS while the other 3 died from other causes. The 2 deaths in TPB were due to causes other than TLS. Risk of mortality from TLS was 30 times higher with TPA than TPB (P=0.0048). Hypertension, seizures, congestive heart failure, bleeding diathesis, severe anaemia, uraemia, proteinuria and microhaematuria were common co-morbidities in the patients. Conclusion: Present data suggest that slow IV infusion of low dose cyclophosphamide given on alternate days in addition to pre-emptive anti-TLS measures were associated with better survival rate (71.4%) in BLARF patients assigned to TPB.